Syaikh Dā’ūd al-Faṭānī dan Hubungan Mekah-Asia Tenggara: Jaringan Intelektual, Transmisi Islam dan Rekonstruksi Sosio-Moral - Burhanudin, Jajat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
Francis R. Bradley. 2016. Forging Islamic Power and Place: The Legacy of Shaykh Dā’ūd ‘Abd Allāh al-Faṭānī in Mecca and Southeast Asia. Honolulu: University of Hawaii Press. 212 pp.This book presents the discussion on Malay Muslim of Patani in southern Thailand today. Taking the social and intellectual life of the father of Patani ‘ulama, Syaikh Dā’ūd ‘Abd Allāh al-Faṭānī (1769-1847), as the main subject of research, this book reveals an important period of Patani history when intellectual activities, centred in Mecca, were transformed into social and moral power for their revival in the 19th and early 20th centuries. The fall of Patani kingdom into the Siamese power in 1786 led the rise of new elites coming from religious circles, the ‘ulama. Under the influence of Syaikh Dā’ūd al-Faṭānī, the ‘ulama engaged in intellectual network and transmission of currently Meccan-based discourses, mainly those in the works of Syaikh Dā’ūd al-Faṭānī, to Patani and Malay peninsula. And this process was strengthened with the rise of pondok, traditional Islamic learning centre, providing the Muslims of Patani with new social and cultural capital for their struggle for identity in the courses of development.DOI: 10.15408/sdi.v24i3.6215